2002
DOI: 10.1086/344526
|View full text |Cite
|
Sign up to set email alerts
|

A Nontoxic Chimeric Enterotoxin Adjuvant Induces Protective Immunity in Both Mucosal and Systemic Compartments with Reduced IgE Antibodies

Abstract: A novel nontoxic form of chimeric mucosal adjuvant that combines the A subunit of mutant cholera toxin E112K with the pentameric B subunit of heat-labile enterotoxin from enterotoxigenic Escherichia coli was constructed by use of the Brevibacillus choshinensis expression system (mCTA/LTB). Nasal immunization of mice with tetanus toxoid (TT) plus mCTA/LTB elicited significant TT-specific immunoglobulin A responses in mucosal compartments and induced high serum immunoglobulin G and immunoglobulin A anti-TT antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 40 publications
2
59
0
Order By: Relevance
“…Our finding that oral delivery of PPE and CT promotes higher levels of peanut-specific IgE responses than nasal delivery is consistent with earlier reports suggesting that Peyer's patches of the GI tract are preferred sites of IgE Ab responses. 50,51 High IgE responses have been reported after nasal administration of mice with several protein antigens in the presence of CT. 34,[52][53][54] High levels of antigen-specific IgE Abs were also measured when OVA was used instead of PPE in our nasal sensitization studies (data not shown). Peanut contains a large number of proteins, and the biological activity of most of them has not been carefully investigated.…”
Section: Discussionmentioning
confidence: 83%
“…Our finding that oral delivery of PPE and CT promotes higher levels of peanut-specific IgE responses than nasal delivery is consistent with earlier reports suggesting that Peyer's patches of the GI tract are preferred sites of IgE Ab responses. 50,51 High IgE responses have been reported after nasal administration of mice with several protein antigens in the presence of CT. 34,[52][53][54] High levels of antigen-specific IgE Abs were also measured when OVA was used instead of PPE in our nasal sensitization studies (data not shown). Peanut contains a large number of proteins, and the biological activity of most of them has not been carefully investigated.…”
Section: Discussionmentioning
confidence: 83%
“…in both C57BL/6 and BALB/c mice (data not shown). Studies with the ganglioside-targeting enterotoxins CT and LT-I (52-55) and derivatives including their chimeras (34,56) or the B cell-targeting CTA1-DD (31,57) have demonstrated the importance of receptor binding for controlling the immune responses induced by these ADP-ribosylating adjuvants. Thus, the adjuvant activity of CT appears to be more dependent on IL-4 and CD4 ϩ Th2 cell cytokines (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The lower stimulatory effect of EdTx for IL-6 secretion was further confirmed in vivo where nasal delivery of CT but not EdTx induced IL-6 secretion in nasal washes. It is unlikely that the reduced ability of EdTx to induce IL-6 (and IL-1) could alone explain the polarized Ag-specific mucosal IgA Abs responses when compared with those generally induced by CT (34,46,63) or LT as adjuvants (34,46,54,56). The role of the adenylate cyclase activity for the adjuvanticity remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…rCTB was expressed in Bacillus brevis and purified by using immobilized galactose (Pierce) (5,37). rLTB was expressed in Brevibacillus choshinensis and purified by using immobilized galactose (Pierce) as previously described, with some modification (38).…”
Section: Methodsmentioning
confidence: 99%